Colloid stabilization by polyelectrolytes application to decotamination process of nulcear reactors - Baumgartner, E.; Torok, J. (Society of Chemical Industry, 1988)
Fil: Baumgartner, E. Comisión Nacional de Energía Atómica; Argentina